Perceived organizational support and job stress on turnover intention: conceptual paper / Roshidah Safeei - Safeei, Roshidah (Universiti Teknologi MARA, Kedah, 2021)
In this era of industrial revolution, employee turnover is a major problem in an organization especially human resource management. It happens in every organization regardless of type of industries and sectors. Employee turnover gives negative effects to an organization. It involves high cost burden for an organization that can be either direct or indirect cost. In today’s competitive business environment, retaining key talented employees is challenging to survive in competitive business environment. In this study, the effect of the perceived organizational support as a managerial practice and the job stress which is caused by the nature of the work on the intention of the employees to leave their work are proposed.